Taxonomy of the genus Antiochtha Meyrick (Lepidoptera, Lecithoceridae) in China, with descriptions of three new species - Yu, Shuai; Wang, Shuxia (European Journal of Taxonomy, 2022)
Antiochtha is a genus of the family Lecithoceridae characterized by the forewing with veins M2 and M3 coincident, the hindwing with vein M2 absent, and the male genitalia with the valva narrowed from base to apex. The genus comprises 23 species and is mainly distributed in the Oriental Region. In this paper, we describe three new species: Antiochtha erromera sp. nov., A. hainanensis sp. nov. and A. miniscula sp. nov., and propose a new synonym, A. rotunda Zhu & Li, 2009 syn. nov., of A. jianfengensis Zhu & Li, 2009. Antiochtha semialis Park, 2002 is newly recorded in China and its female is described for the first time.